The Influence of Organizational Culture, Work Discipline, and Job Training on Employee Performance At Pt. Light of Son of Saka - Hasanah; Sunarti; Mulyati; Yuliantoro, Tri (Jurnal Ekonomi dan Bisnis Digital, 2024)
The purpose of this study is to ascertain and evaluate the effects of work discipline, job training, organizational culture, and all three on employee performance. The study employed a quantitative research design, with a sample size of 49 employees using saturated samples and non-probability sampling. Both The sources of data were both primary and secondary instrument-based data analysis technique testing with validity and reliability tests; by testing classical assumptions, namely data normality, heteroscedasticity and multicollinearity; as well as partial and simultaneous statistical testing. According to the study's findings, job training has a positive and significant impact on the performance of PT employees; similarly, organizational culture has a positive and significant impact on employee performance as well as work discipline. The Enlightenment of the Son of Saka. Meanwhile, simultaneously organizational culture, The combination of work training and work discipline has a favorable and noteworthy impact on employee performance.